Leveraging IoT and dedicated social networks to enhance mosque role and activities management in Saudi Arabia - Nawal Almutairi; Abdussalam Elhanashi (Digital Business, 2025)
This paper examines the challenges encountered in mosques activities management and explores the potential use of internet of things. To this end, qualitative methods, surveys and semi-structured interviews, were conducted. The results reveal key challenges, which are related to mosque accessibility, communication, and engagement in decision-making. As a part of the proposed solution, the Mehrab system incorporates a dedicated social networking, smart locks, and smart key delegation. Mehrab was developed using an Agile methodology that involves potential users throughout the development process to ensure the inclusion of essential features aligned with the system's objectives. Mehrab was tested by 400 participants who performed a set of tasks that covered the core functionalities and then answered questionnaires to evaluate application objectives achievement, usability, and technology acceptance. Statistical analysis revealed that participants' evaluations of system objectives differed significantly from a neutral benchmark, indicating a positive perception. A system usability scale survey was used to assess usability, and we achieved an excellent result of 94.23, exceeding the threshold to pass the test. To assess technology acceptance, the technology acceptance model was integrated with institutional theory, offering a robust framework for understanding acceptance factors in religious settings. Regression analysis showed that perceived usefulness, attitude toward using technology, and behavioral intention were the strongest predictors of actual use which commonly interpreted as indicators of technology acceptance, while institutional factors, including normative and coercive pressures, also had significant influence. Moreover, sentiment analysis was employed to measure users' opinion, which indicated that 94.5% of participants had positive opinions.
Keywords: 650; Digital transformation; Digitalization; Institutional theory; Internet of things (IoT); Smart cities; Smart mosques; Technology acceptance model (TAM)